Public-private partnerships – a risk approach in the water sector - Lima, S.; Brochado, A.; Marques, R. C. (5th International Conference on WATER ECONOMICS, STATISTICS and FINANCE, 2021)
Abstract: This study provides a contribution on how public-private partnership arrangements can more efficiently address risk. The perception of risk management by different stakeholders is presented. The results are based on semi-open interviews performed to public-private partnership experts. Literature suggested five risk categories, namely financial, context, technical and operational, commercial and infrastructure. Twenty-five risk factors with high impact were established as a result of the semi-interviews. The top-five critical risk factors are related to political interference, no baselines for measurement performance, unfavourable global private investment climate, non-payment of bills and water asset condition uncertainty. The traditional risk management approach in public-private partnerships contracts have space to improve. Study results supported that risk category context ranked first, nevertheless, emergent topics such infrastructure risk category are equally relevant